Investigation of the effect of the excipients quantitative characteristics on the main indicators of ophthalmic/otologic suspension quality - Zavalko, I. V. (Zaporozhye Medical Journal, 2013)
Quantitative factors of excipients for suspension were investigated. Their influence on pharmaco-technological parameters of drug was studied.